Challenges and Opportunities for Primary Teachers in Implementing NEP 2020’s Vision for Quality Education: E-learning Perspective - Saxena, Neha; Gupta, Kiran Gupta; Nagi, Bishan Singh (THE PRIMARY TEACHER, 2022)
The introduction of India’s National Education Policy 2020 (NEP 2020) has led to a significant change, emphasising a modern and comprehensive approach to education. A central aspect of this policy is the integration of technology, particularly the advancement of quality e-learning. Within the framework of implementing NEP 2020’s vision for quality e-learning, it is essential to acknowledge the challenges and opportunities faced by primary teachers. E-learning has the potential to revolutionise education, providing equal access in a diverse and vast nation like India, where traditional educational resources are often inaccessible in various areas. This paper explores the various dimensions of this transformation, highlighting the important role of e-learning in achieving NEP 2020’s objectives while emphasising the role of primary teachers in adapting to this evolving educational landscape